Permeability and antifouling augmentation of a hybrid PVDF-PEG membrane using Nano-magnesium oxide as a powerful mediator for POME decolorization - Abdulsalam, Mohammed; Che Man, Hasfalina; Goh, Pei Sean; Yunos, Khairul Faezah; Zainal Abidin, Zurina; Isma M.I., Aida; Ismail, Ahmad Fauzi (Multidisciplinary Digital Publishing Institute, 2020)
This study focused on developing a hydrophilic hybrid polyvinylidene fluoride (PVDF)-polyethylene glycol (PEG) hollow membrane by incorporating Nano-magnesium oxide (NMO) as a potent antifouling mediator. The Nano-hybrid hollow fibers with varied loading of NMO (0 g; 0.25 g; 0.50 g; 0.75 g and 1.25 g) were spun through phase inversion technique. The resultants Nano-hybrid fibers were characterized and compared based on SEM, EDX, contact angle, surface zeta-potential, permeability flux, fouling resistance and color rejection from palm oil mill effluent (POME). Noticeably, the permeability flux, fouling resistance and color rejection improved with the increase in NMO loading. PVDF-PEG with 0.50 g-NMO loading displayed an outstanding performance with 198.35 L/m2·h, 61.33 L/m2·h and 74.65% of water flux, POME flux and color rejection from POME, respectively. More so, a remarkable fouling resistance were obtained such that the flux recovery, reversible fouling percentage and irreversible fouling percentage remains relatively steady at 90.98%, 61.39% and 7.68%, respectively, even after 3 cycles of continuous filtrations for a total period of 9 h. However, at excess loading of 0.75 and 1.25 g-NMO, deterioration in the flux and fouling resistance was observed. This was due to the agglomeration of nanoparticles within the matrix structure at the excessive loading.